Neonatal Hypopituitarism: Approaches to Diagnosis and Treatment - Selim Kurtoğlu; Ahmet Özdemir; Nihal Hatipoğlu (JCRPE, 2019)

(untitled)
Hypopituitarism is defined as a decreased release of hypophyseal hormones, which may be caused by disease of the pituitary gland disease or hypothalamus. The clinical findings of neonatal hypopituitarism depend on the causes and on presence and extent of hormonal deficiency. Patients may be asymptomatic or may demonstrate non-specific symptoms, but may still be at risk for development of pituitary hormone deficiency over time. Patient history, physical examination, endocrinological, radiological and genetic evaluations are all important for early diagnosis and treatment. The aim of this paper was to present a review of etiological factors, clinical findings, diagnosis and treatment approaches in neonatal hypopituitarism.